Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Kepuasan Pelanggan Warkop Sawah Kopi Desa Tanjungsari Boyolangu Tulungagung - Muhammad Cahya Hadi Sudrajad; Imam Sukwatus Suja’i (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
In the current era, economic factors have become essential in meeting human needs. Therefore, people meet their economic needs by engaging in business activities. One of the famous businesses in Tulungagung Regency is the coffee shop business. Coffee shops in Tulungagung Regency are abundant and even well-known beyond the regency itself. This study aims to determine the influence of service quality on customer satisfaction, the influence of facilities on customer satisfaction, and to understand the influence of service quality and facilities on customer satisfaction at Warkop Sawah Kopi in Tanjungsari Village, Boyolangu, Tulungagung. This research is a quantitative correlational study with a non-experimental approach. The study consists of two independent variables, namely service quality and facilities, and one dependent variable, customer satisfaction. The results of the partial hypothesis test (t-test) show that the significance value is, while facilities have a significant t-value. The results of the F-test show a significant F-value. It can be concluded that service quality has a positive and significant partial effect on customer satisfaction, facilities have a positive and significant partial effect on customer satisfaction, and both service quality and facilities have a simultaneous positive effect on customer satisfaction.